Makna Naga Dalam Iklan Marjan 2023 “Baruna Sang Penjaga Samudera” - Syafruddin Pohan; Rima Ivana (Pusat Riset dan Inovasi Nasional, 2023)
Advertising is one of the mass communication media in the form of visual, audio, writing, or a combination of audio-visual. As with any communication in general, every advertisement must have an implicit or explicit meaning contained therein which is addressed to the public. Marajan as one of the syrup products in Indonesia, often makes advertisements that are full of meaning with attractive packaging. The purpose of this study is to find out the meaning of the dragon in Marjan 2023 advertisement